Digital Leadership and Teacher Digital Competence as Keys to Successful Integration of Digital Culture in Education - Lukman, Faizal; Yune, Evan Keandre (Islamic Educational Management Programme, 2025)
This study investigates the critical role of digital leadership and teacher digital competence in the successful integration of digital culture in education. Previous research has not sufficiently explored the correlation between digital leadership and teacher competence, particularly in the educational context of Southeast Asia, where these elements have remained understudied. The research was conducted at SMAN 1 Kutacane, Southeast Aceh, Indonesia, analyzing the influence of digital leadership and teachers' digital competence on the integration of digital culture. Using a mixed method, this study combines qualitative and quantitative approaches. Data were collected through surveys of 100 teachers and 50 students and in-depth interviews with 10 teachers. The results of the analysis show that digital leadership has a positive effect on teachers' digital competence, which in turn promotes the effective integration of digital culture in the educational environment. The findings of this study emphasize the importance of digital leadership for educational policymakers and school administrators, suggesting the need for targeted teacher competence development programs. Therefore, the findings are expected to guide the design of effective strategies for integration digital culture.